Les constructions bàties sur les noms de relations converses -principes d’analyse syntagmatique - Nkollo, Mikołaj (Studia Romanica Posnaniensia, 2017)
Structural modeling of sentences based on the nouns of converse relations has to be designed so as to take into account the diversity of syntactic functions covered by this class of language signs. It implies taking into consideration particular features of pairs of converse relations depending on the part of speech they represent. Fundamental methodological assumptions of this approach are to be sought in socalled "semantically based grammar".